ECONOMIC EDUCATION STRATEGIES FOR IMPROVING MSME INCOME THROUGH DIGITALIZATION - Hidayat, A. Taufiq; Makhmut, Khalilah Daud Isaac; Azizah, Laila Nur (EDUCATUM: Scientific Journal of Education, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are productive businesses owned by individuals or small business entities with certain limitations in terms of assets and turnover, in accordance with Law Number 20 of 2008 concerning Micro, Small, and Medium Enterprises (MSMEs) which act as the backbone of the Indonesian economy with a large contribution to Gross Domestic Product (GDP) and employment opportunities. Micro, Small, and Medium Enterprises still face various challenges, such as low digital literacy, as well as difficulties in marketing and product innovation. The use of technology can be a solution for Micro, Small, and Medium Enterprises to increase competitiveness and expand the market. This study aims to analyze the role of digitalization and product innovation in increasing the income of Micro, Small, and Medium Enterprises. The research method used is descriptive qualitative with a case study approach on Micro, Small, and Medium Enterprises in the food and service sectors. Data were obtained through interviews, observations, questionnaires, and supporting literature. The results of the study indicate that the application of digitalization, such as the use of e-commerce, social media, and digital payment systems, can expand market reach and improve operational efficiency. This is proven by the research sample of 10 Micro, Small, and Medium Enterprises (MSMEs) significantly increased in terms of income. Thus, digital transformation is an important strategy that needs to be implemented sustainably by Micro, Small, and Medium Enterprises to support inclusive economic growth..